2012
DOI: 10.3109/0142159x.2012.651178
|View full text |Cite
|
Sign up to set email alerts
|

Post-examination interpretation of objective test data: Monitoring and improving the quality of high-stakes examinations: AMEE Guide No. 66

Abstract: The purpose of this Guide is to provide both logical and empirical evidence for medical teachers to improve their objective tests by appropriate interpretation of post-examination analysis. This requires a description and explanation of some basic statistical and psychometric concepts derived from both Classical Test Theory (CTT) and Item Response Theory (IRT) such as: descriptive statistics, explanatory and confirmatory factor analysis, Generalisability Theory and Rasch modelling. CTT is concerned with the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…This function is depicted graphically in an ICC. We have already shown how to draw the ICC elsewhere (Tavakol & Dennick 2012a, 2012b. We indicated that if the student ability is equal to the item difficulty (B-D ¼ 0), the probability that the student will answer the question correctly is 50% which can be seen in the ICC.…”
Section: Item Characteristic Curvementioning
confidence: 99%
See 2 more Smart Citations
“…This function is depicted graphically in an ICC. We have already shown how to draw the ICC elsewhere (Tavakol & Dennick 2012a, 2012b. We indicated that if the student ability is equal to the item difficulty (B-D ¼ 0), the probability that the student will answer the question correctly is 50% which can be seen in the ICC.…”
Section: Item Characteristic Curvementioning
confidence: 99%
“…For example, in a test we would not expect to see low performing students having a high probability of answering a given item correctly. We have explained how to draw an ICC using student ability and item ability elsewhere (Tavakol & Dennick 2012a, 2012b …”
Section: The Rasch Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Further information on the impact of scoring rubrics can be found in AMEE Guides 49, 54 and 66 (Pell et al 2010;Tavakol & Dennick 2011;Tavakol & Dennick 2012).…”
Section: Details Of Their Concerns/perceptionsmentioning
confidence: 99%
“…Table 2 lists frequently used parameters for quantitative evaluation for each level. Statistical details are available in a comprehensive guide from the Association for Medical Education in Europe [32].…”
Section: Perform Post Hoc Analysismentioning
confidence: 99%